1998
DOI: 10.3102/01623737020003197
|View full text |Cite
|
Sign up to set email alerts
|

Helping the Progress of Disadvantaged Students in Higher Education: The Federal Student Support Services Program

Abstract: Student Support Services (SSS) is one of the largest federal TRIO programs designed to help disadvantaged students stay in and complete college. Through a longitudinal study of participants and comparable non participants, we examined the impact of SSS on retention. Data were collected through student questionnaires, institutional and program data, and students’ postsecondary transcripts. We found that SSS had a positive impact for all three measures of retention that were used, but the impact varied depending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 6 publications
4
30
0
Order By: Relevance
“…That being said, researchers are still trying to understand exactly how such programs work and what array of programs and services are best for which students (Balz and Esten 1998;Chaney et al 1998). Where Chris and Ty seemed to benefit from the comprehensive social and academic services provided by 'Aspire', Jason O-Bannon seemed to suffer from the extent to which his participation in 'Crew-10' curtailed his ability and/or desire to form more extensive ties on campus.…”
Section: Discussionmentioning
confidence: 92%
“…That being said, researchers are still trying to understand exactly how such programs work and what array of programs and services are best for which students (Balz and Esten 1998;Chaney et al 1998). Where Chris and Ty seemed to benefit from the comprehensive social and academic services provided by 'Aspire', Jason O-Bannon seemed to suffer from the extent to which his participation in 'Crew-10' curtailed his ability and/or desire to form more extensive ties on campus.…”
Section: Discussionmentioning
confidence: 92%
“…The validation models reflect the relationship between engagement and GPA, controlling only for institutional and year-to-year differences in survey administrations. One notable exception to the positive relationship between GPA and engagement constructs was in the factors comprised largely of student services, a factor that has been associated with retention in previous research (Chaney et al, 1998). An explanation for the lack of effect attributable to this construct is the possibility that student services are not always directly related to learning.…”
Section: Reliability and Validity Of The Ccsrmentioning
confidence: 91%
“…Active learning activities, such as class discussions, have a positive relationship with student persistence (Braxton, Milem, & Sullivan, 2000). Use of student support services, such as peer counseling, positively impacts student retention (Chaney, Muraskin, Cahalan, & Goodwin, 1998). Academic and out-of-class experiences have been shown to contribute to gains in intellectual orientation and curiosity after controlling for precollege characteristics (Terenzini, Springer, Pascarella, & Nora, 1995).…”
Section: Theoretical Basis Of the Community College Student Reportmentioning
confidence: 97%
“…Interestingly, some previous studies (e.g. Chaney et al, 1998;Schurr et al, 1993) have found that participants or spectators in campus recreation or sports were more likely to persist in college than nonparticipants or attenders. Thus, attendance at all types of campus events indicates social integration with the campus because it provides excellent opportunities for students to socialize outside of classes.…”
Section: Social Integrationmentioning
confidence: 97%
“…For example, McGrath and Braunstein (1997) found that receiving financial aid predicted students' GPA. In a study of several retention programs throughout the USA, over half of the students who left the university indicated that insufficient funds were the cause (Chaney et al, 1998). Although low family income may not directly decrease some students' persistence in college, student persistence in school and academic achievement can be adversely affected by a heavy workload (Canabal, 1995b;Di, 1996).…”
Section: Background Variablesmentioning
confidence: 99%